POLA PENGOBATAN DAN FAKTOR - FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN MINUM OBATPADA PASIEN TUBERKULOSIS DI RSUD KOTA BEKASI PERIODE SEPTEMBER - NOVEMBER 2019 - Maudhira Anindita, (2020)
Indonesia is ranked as having the third place highest TB burden in the world after India and China. The high incidence of pulmonary TB become a health problem in community that required disease control. The DOTS strategy for controlling TB is the most effective strategy. Nonadherence to medication in TB patients can cause fail treatments and developing MDR-TB. The purpose of this study to determine factors affecting medication adherence among TB patients in RSUD Kota Bekasi in September - November 2019. The design of this study is a cross-sectional method with a sample size of 134 patients who meet the inclusion criteria with consecutive sampling. MMAS-8, knowledge, roles of the health care provider and family support questionnaires were used to collect the data along with the demographic data. The results of this Chi-square analyzes indicate the are factors affecting high medical adherence are patients' age (p value=0,001; OR=0,019 95% CI 0,007-0,057), gender (p value=0,026; OR=2,330 95% CI 1,098-4,940), high education level (p value=0,001; OR=5,766 95% CI 2,487-13,365), high income (p value=0,001; OR=14,913 95% CI 3,392-65,566), early treatment phase (p value=0,001;OR=12,656; 95% CI 4,180-38,318), duration of treatment <6 months (p value=0,001; OR=0,027 95% CI 0,009-0,085), patterns of usage FDC regimens (p value=0,001; OR=13,459 95% CI 2,867-63,178), good knowledge (p value=0,001; OR=63,438 95% CI 20,799-225,184), roles of health care provider supports (p value=0,002; OR=8,594 95% CI 18,640-393,043) and high family support (p value=0,001; OR=15,188 95% CI 2,204-37,458). Logistic regression analyzes showed that family support is the dominant factor in affecting medication adherence of pulmonary TB patients (odds ratio 8,173; 95% CI 15,166-45.104).